The synergistic effect of oxaliplatin and punicalagin on colon cancer cells Caco-2 death - Alsufiani, Hadeil (International Journal of Health Sciences, 2024)
Objectives: The objectives of the study are to investigate the synergistic effect of oxaliplatin (oxa) and punicalagin (pun) on the death of colon cancer cells (Caco-2) by apoptosis and autophagy. Methods: The effects of the combined treatments (5 μM oxa + 50 μM pun, 5 μM oxa + 75 μM pun, 20 μM oxa + 50 μM pun, and 5 μM oxa + 75 μM pun) were compared with untreated Caco2 cells (control) or cells treated with oxa alone. Apoptosis was detected using an Annex in V FITC flow cytometry assay and poly (ADP-ribose) polymerase cleavage by western blotting. Light chain 3 was detected by western blotting as an autophagy marker. Results: The combined treatments significantly increased the number of apoptotic cells in comparison to untreated cells or cells treated with oxa alone. By contrast, the combined treatments had no significant effect on autophagy. Conclusion: The combined treatment significantly promoted cell death through apoptosis while maintaining a basal level of autophagy.